880-nm-Diode-Laser-End-Pumped Electrooptically Q-Switched Nd:YLF Laser With High Energy and Good Beam Quality at 1047 nm and 1 kHz - Zilong Zhang; Qiang Liu; Mingming Nie; Encai Ji; Mali Gong (IEEE Photonics Journal)
An electrooptically Q-switched Nd:YLF laser end-pumped by an 880-nm laser diode with high energy and short pulsewidth at 1 kHz is demonstrated. The asymmetry of the focal lengths of thermal lens along the $a$ -axis and $c$ -axis is observed, and the cylindrical lens is used to compensate for the thermal lens effect along the $a$ -axis. We experimentally studied the performance of the Nd:YLF laser with different combinations of the output coupler transmission $T$ and the focal length $f$ of cylindrical lens. With $T=40%$ and $f=300\ \text{mm}$ , 9.5-mJ pulse energy, 9.5-ns pulsewidth, and beam quality factors of $M_{x}^{2}=1.74$ and $M_{y}^{2}=1.97$ are obtained. Moreover, the relationships between the pulse width and pump power as well as beam transverse mode were experimentally studied and discussed.